Respuesta :
We are given
x² + 3y² = 8 + 2xy
We are asked for
d^2y/dx^2 at (2,2)
Which is the second derivative of the expression in terms of x evaluated at (2,2)
The expression can't be express explicitly in terms of x
Doing implicit differentiation
2x dx + 6y dy = 2y dx + 2 x dy
Solving for dy/dx
dy/dx = (2x - 2y) / (2x - 6y)
Then,
d^2y/dx^2 at (2,2) can now be determined
x² + 3y² = 8 + 2xy
We are asked for
d^2y/dx^2 at (2,2)
Which is the second derivative of the expression in terms of x evaluated at (2,2)
The expression can't be express explicitly in terms of x
Doing implicit differentiation
2x dx + 6y dy = 2y dx + 2 x dy
Solving for dy/dx
dy/dx = (2x - 2y) / (2x - 6y)
Then,
d^2y/dx^2 at (2,2) can now be determined
Answer:
The value of [tex]\frac{d^2y}{dx^2}[/tex] at (2,2) is [tex]\frac{-1}{4}[/tex].
Step-by-step explanation:
The given equation is
[tex]x^2+3y^2=8+2xy[/tex]
Differentiate with respect to x.
[tex]2x+3(2yy')=0+2(xy'+y)[/tex]
Here, [tex]y'=\frac{dy}{dx}[/tex]
[tex]2(x+3yy')=2(xy'+y)[/tex]
[tex]x+3yy'=xy'+y[/tex]
[tex]3yy'-xy'=y-x[/tex]
[tex](3y-x)y'=y-x[/tex]
[tex]y'=\frac{y-x}{3y-x}[/tex]
The value of first derivative at (2,2) is
[tex]y'_{(2,2)}=\frac{2-2}{3(2)-2}=0[/tex]
Differentiate with respect to x. Using quotient rule we get,
[tex]y''=\frac{(3y-x)(y'-1)-(y-x)(3y'-1)}{(3y-x)^2}[/tex]
The value of second derivative at (0,0) is
[tex]y''_{(2,2)}=\frac{(3(2)-2)(y'_{(2,2)}-1)-(2-2)(3y'_{(2,2)}-1)}{(3(2)-(2))^2}[/tex]
[tex]y''_{(2,2)}=\frac{(4)(0-1)-0}{4^2}[/tex]
[tex]y''_{(2,2)}=\frac{-4}{16}[/tex]
[tex]y''_{(2,2)}=\frac{-1}{4}[/tex]
Therefore the value of [tex]\frac{d^2y}{dx^2}[/tex] at (2,2) is [tex]\frac{-1}{4}[/tex].